2017
DOI: 10.1063/1.4977717
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dy sub lattice dilution on transport and magnetic properties in Dy1-xKxMnO3

Abstract: Interaction of multiple oxidation states of manganese ions with rare earth ions in manganites leads to the observation of various magnetic ground states. To understand the effect of average ionic size on electrical conductivity and magnetic ground state properties in Dy1-xKxMnO3 (x=0.0, 0.1, 0.2 & 0.3), we have investigated electron transport as a function of temperature and magnetic properties as a function of temperature, frequency and magnetic field of these compounds. Although mixed valent manganese io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The above behaviours should be ascribed to the canting of magnetic spins in range of magnetic transition temperature. Similar results can also be observed in the latest studies of spin frustrated antiferromagnets materials [31]. From Figure 6, it should be noted that the value of saturation magnetisation (Ms) of the experimental samples exhibits quite different, from 3.65 to 23.22 emu g −1 .…”
Section: Magnetic Propertiessupporting
confidence: 86%
“…The above behaviours should be ascribed to the canting of magnetic spins in range of magnetic transition temperature. Similar results can also be observed in the latest studies of spin frustrated antiferromagnets materials [31]. From Figure 6, it should be noted that the value of saturation magnetisation (Ms) of the experimental samples exhibits quite different, from 3.65 to 23.22 emu g −1 .…”
Section: Magnetic Propertiessupporting
confidence: 86%
“…The anti-parallel spin ordering in CFOs may be affected by vacancies, improving their magnetic properties; (3) the substitution of Fe by Mn in CFOs can change the bond lengths and angles, changing the inclination angle of FeO 6 octahedron, which modulates the system's magnetic spin and improves the magnetic properties; (4) the greater the Fe 3+ ion content, the greater the magnetization. Compared with the studies on Ti-doped CFO [32], in cases of the same valence ion substitution, the magnetic structure deformation caused by small-size ion doping, and the competitive effect among ions of different magnetic moments is more significantly conducive to improving the magnetic properties of CFO systems. In conclusion, changes in the microstructures, grain sizes, charge compensation, and magnetic moments of different ions are important factors affecting the magnetic properties of CFO systems.…”
Section: Magnetic Propertiesmentioning
confidence: 83%
“…The samples' magnetization is unsaturated under the measured field of 0.5, indicating the presence of multiple magnetic interactions [31]. The x = 0.00-0.03 samples' M-H curves exhibit linear field-dependent magnetization, indicating their antiferromagnetic behavior, while the x = 0.05-0.10 samples demonstrate typical and symmetric hysteresis loop characteristics, indicating the presence of weak CFO-based ferromagnetism due to the short-range Fe-O-Fe interactions induced by Mn doping [28,32].…”
Section: Magnetic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…3(a) shows temperature dependence of electrical resistivity, r(T) of Dy 1Àx Eu x MnO 3 from 150 K to 300 K. It is observed that the semiconducting behavior persists in the whole temperature range of measurement. In order to understand the charge transport mechanism for the observed semiconducting behavior, various models such as thermal activation process involving nearest neighbor hopping 23,24 (Arrhenius law), hopping of small polarons (SPH) in the adiabatic approximation [25][26][27] and variable range hopping 28 (VRH) conduction process were used to t the r(T) data. The equation for thermal activation process for nearest neighbor hopping conduction with activation energy (E a ) is given by Arrhenius equation: …”
Section: Resultsmentioning
confidence: 99%